2018
DOI: 10.21037/jtd.2018.01.79
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogressive disease in patients with non-small cell lung cancer on immunotherapy

Abstract: Immunotherapy agents in metastatic non-small cell lung cancer (NSCLC) can result in improved quality of life and survival when compared with platinum-based chemotherapy. Novel response patterns such as pseudoprogression and hyperprogression, however, have been described and pose a challenge to treating physicians. Predictors of hyperprogressive disease (HPD) have not yet been identified. Evaluation and management by a multidisciplinary team involving medical and radiation oncologists, thoracic radiologists, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…Combination treatment modality and clinical unmet needs, being the two major aspects, were ideal resolutions for the development of novel CPIs. To be noticed, challenges to immunotherapy remained to be unsolved including hyperprogression [244,245], immune-related toxicities [246,247], and primary/adaptive resistance to immunotherapy [248]. Moreover, potential novel treatment modalities have aroused great interest and their preliminary performances revealed remarkable prospects for development in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Combination treatment modality and clinical unmet needs, being the two major aspects, were ideal resolutions for the development of novel CPIs. To be noticed, challenges to immunotherapy remained to be unsolved including hyperprogression [244,245], immune-related toxicities [246,247], and primary/adaptive resistance to immunotherapy [248]. Moreover, potential novel treatment modalities have aroused great interest and their preliminary performances revealed remarkable prospects for development in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Progression is defined as an increase in tumour size (which is the summation of the longest diameter of five target lesions) of more than 20% compared to the lowest determined tumour size at any point in time. The possibility of pseudo-progression [4][5][6] necessitated a second update of RECIST and in 2017, iRECIST was adopted as a novel tumour response evaluation tool in patients with immunotherapy treatment [7]. Several authors have suggested that RECIST criteria may be inadequate to capture the response to immunotherapies [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, like other therapies, PD-1/PD-L1-targeted antibody therapies may lead to side effects and toxicities, which mainly include immune-related adverse events associated with inflammatory conditions (18) and cardiac toxicity (19). Notably, two atypical responses, i.e., hyperprogressive disease (HPD) and pseudoprogressive disease (PPD) have been observed after the ICT (20,21). This evidence demonstrates that the mechanism underlying ICT targeting PD-1/PD-L1 remains incompletely understood.…”
mentioning
confidence: 99%